Investigating User Intention to Commute Using Autonomous Rail Transit in Johor - Tan, Wei Jie (Universiti Malaysia Sarawak (UNIMAS), 2022)
Autonomous rail transit is an important indicator for evaluating urban development from people of all work of life. Therefore, it had become a vogue topic for the public figure especially in the field of transportation. In this research, researcher will be mainly examining the relationship between social norm, attitude, perceived behavioural control, reliability, environmental concern and tangibles